FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ANGKA KUMAN PADA PERALATAN MAKAN DI RUMAH MAKAN WILAYAH PERIMETER DAN BUFFER AREA PELABUHAN SAMPIT - Khafid Anwar Cholid; Yusniar Hanani Darundiati; Sulistiyani Sulistiyani (Jurnal Kesehatan Masyarakat (Undip), 2022)
Sampit Seaport is a berth for various kinds of ships, including passenger ships, cargo ships, Crude Palm Oil ships. In 2019 of 15 eating utensil that was inspected  the number of germs as many as 13 eating utensil unqualified of health and there are reports  1 prospective ship passenger who experienced diarrhea during Lebaran homecoming. Monitoring the bacteriological quality of eating utensil is one of the keys to prevent foodborne diseases. This study aims to determine the factors associated to the number of bacteria on eating utensil including washing water, eating utensil materials, eating utensil  washing techniques, eating utensil drying techniques and eating utensil storage at Sampit Seaport. This was an observational study with a cross-sectional design. The population in this study were all of the eating utensil in 10 restaurants located in the perimeter and buffer area of the Sampit Seaport. The number of samples in this study were 60 eating utensil. Data analysis was univariate and statistical test using the Pearson Chi Square. The results showed that 28 (46.67%)  did not meet the bacteriological requirements. The results of statistical analysis showed that there was a association between washing water (p=0.013), The results showed that 46.67% is unqualified the bacteriological requirements storage  (p=0.001) to the total plate number on eating utensil. In addition, there was no association between eating utensil material (p=0.560), washing technique (p=0.174), and drying technique (p=0.174) with the Total Plate Number on eating utensil. It can be concluded that there was a associationbetween washing water and storage of eating utensil to total palre count on eating utensil. Suggestions for restaurants is to pay attention of sanitation hygiene to eating utensil that used in the restaurant.